Committing Crime to Attend Online Class: Elucidating News Media’s Polemic on Covid-19 Distance Learning Policies - Yandra, Alexsander; Husna, Khuryatul; Masyitah, Wan; Oktaviani, Ira; Derin, Tatum (Utamax : Journal of Ultimate Research and Trends in Education, 2022)
Educational research papers that explored Covid-19 have naturally focused on the problems of distance learning implementation but also underscores its severe impacts. This study aims to demonstrate the polemic against Covid-19 distance learning policies within news media outlet. The method of this qualitative study is a literature review on 5 newspaper media and 10 online media to obtain data of news items on Covid-19 distance learning that were published from April to December 2020 (9 months). This study tracked 82 news items from newspaper media and 191 news items from online media and determined three trends across all of the news items: obstacles, impact and policies of distance learning. Results showed that the implementation of distance learning is still far from expectations due to the lack of communication between the government and the school, the lack of human resources and supporting facilities, and the non-existent supervision towards schools that ignore the policies. This paper contributed in delivering the obstacles that arise from and because of distance education policies that news media report to the public.